Exploring Digital Storytelling as a Pedagogy Approach: Literature and Language Teaching - Rama Devi P (Digital Crossroads: Integrating Humanities, Science and Technology Edition 1, 2025)
This paper discusses an exploration of the effect of digital storytelling as a pedagogy approach for secondary school-level English literature and language teaching. Twenty students from Sarada High School, Narsipatnam, who are pursuing ninth standard, form the sample of the study. The main objective of the study is to increase engagement and motivation in learning language and literature and provide Alternative Assessment Opportunities (AAO) as well. A review of the literature is performed to look into the previous studies on alternative assessments in literature and language education by using a qualitative research approach. By exploring this from a mixed-methods research design based on quantitative assessments combined with qualitative analysis, this paper gives insight into the impact on vocabulary acquisition, narrative structure understanding and total language fluency through digital storytelling. Statistical Package for the Social Sciences (SPSS) and NVivo are the tools employed for the study. The results aimed to identify some of the key benefits of using digital storytelling in the education system. In contrast, a few drawbacks are associated with the need to train teachers on the use of technology and issues related to the assessment of students with different access to technology. Some gaps have been identified along with suggestions for using digital storytelling to address them within literature and language curricula. This paper is a contribution to the ever-growing body of literature in support of digital storytelling as a transformative education tool that prepares students for the challenges of 21st-century communication and literacy.